2017 CSI Handbook – 20th Edition - (:unkn) unknown (Trialogue Publication, 2017)
Chapter 4: Local and global perspectives Criteria for determining strategic CSI and a profile of the recipient of the Trialogue Strategic CSI Award 2017, insights from The Trialogue Business in Society Conference 2017, key findings from CSI research conducted in Ghana and Kenya, and trends in global corporate giving.
Keywords: 2017 CSI Handbook; CSI in Ghana and Kenya